2022
DOI: 10.18502/cmm.8.1.9210
|View full text |Cite
|
Sign up to set email alerts
|

Candidemia: Changing dynamics from a tertiary care hospital in North India

Abstract: Background and Purpose: Routine identification of Candida species and knowledge of antibiotic susceptibility patterns can prevent diagnostic delays and help clinicians choose appropriate empirical therapies. This study aimed to identify and speciate Candida isolates from bloodstream infections and evaluate their epidemiological profile and antibiotic susceptibility pattern in a tertiary care hospital in North India. Materials and Methods: Blood samples were cultured in the Department of Microbiology of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 17 publications
(37 reference statements)
1
5
0
Order By: Relevance
“…During the pre-pandemic period, the profile of the involved Candida spp. was in complete agreement with the other global studies of Kaur et al, (2020); Alhatmi et al, (2022); Gautam et al, (2022), where prevalence of NAC was being much higher than C. albicans (89 % vs 11 %).…”
Section: Prevalence Of Candidemia Over the Different Study Periodssupporting
confidence: 93%
See 1 more Smart Citation
“…During the pre-pandemic period, the profile of the involved Candida spp. was in complete agreement with the other global studies of Kaur et al, (2020); Alhatmi et al, (2022); Gautam et al, (2022), where prevalence of NAC was being much higher than C. albicans (89 % vs 11 %).…”
Section: Prevalence Of Candidemia Over the Different Study Periodssupporting
confidence: 93%
“…The epidemiology of candidemia is constantly evolving. The shift in the causative species causing candidemia from C. albicans to Non albicans Candida (NAC) has been documented on a global level (Kaur et al, 2020;Alhatmi et al, 2022;Gautam et al, 2022). New multidrug resistant species such as C. auris are being reported in the previous study conducted by Chowdhary et al, (2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, species identification was only performed using traditional tests and is therefore uncertain. Two retrospective studies from India reported the presence of W. anomalus in clinical yeast collections from patients with varying predisposing conditions (Gautam et al 2022;Saha et al 2022). Both studies employed traditional biochemical tests for species identification, but no molecular confirmation.…”
Section: Wickerhamomyces Anomalusmentioning
confidence: 99%
“…From 154 isolates, seven of them were identified as D. hansenii. Gautam et al (2022) isolated yeasts from 0 to 1-month-old neonates, infants and children in the age range of 1-17 years. Among isolates from a total of 116 blood samples, D. hansenii made up 9.48%.…”
Section: Debaryomyces Hanseniimentioning
confidence: 99%
See 1 more Smart Citation